2020
DOI: 10.34293/education.v8i4.3260
|View full text |Cite
|
Sign up to set email alerts
|

Questioning Techniques and Teachers’ Role in the Classroom

Abstract: The aim of this study is to discuss the efficacy of questioning techniques of the teachers in the classroom. Proper questioning techniques are important in the teaching and learning process. Proper questioning techniques will make it easier for teachers to get feedback from students whether or not they understand the subject. This article describes some of the questioning techniques that a teacher needs to know to possess in classroom teaching and learning sessions such as attention, suitable voice. Pause, que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 0 publications
0
16
0
4
Order By: Relevance
“…On the relevance of questioning, it is reported that questioning is an important classroom activity (Shanmugavelu, 2020) [16] , and that "Almost every teaching method requires the use of questioning" (Alorvi, 2014) [3] . Since teaching generally involves complex tasks, it is important for teachers to plan for the kind of questions they would want students to answer during lesson delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the relevance of questioning, it is reported that questioning is an important classroom activity (Shanmugavelu, 2020) [16] , and that "Almost every teaching method requires the use of questioning" (Alorvi, 2014) [3] . Since teaching generally involves complex tasks, it is important for teachers to plan for the kind of questions they would want students to answer during lesson delivery.…”
Section: Discussionmentioning
confidence: 99%
“…To stimulate a high level of thinking, research in the area of questioning suggests that "Teachers must play a key role in applying the right techniques and skills to question students" (Shanmugavelu, 2020) [17] . In light of this, it is essential for teachers to adopt effective questioning strategy as a way to keep students actively engaged in the teaching and learning process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In learning environments, the way lecturers conduct classes may influence how the students behave in terms of knowledge-sharing behavior (Yogeesha & Krishna, 2013). Stimulation of questions and answers from students by lectures in question-and-answer sessions may help students test their knowledge (Shanmugavelu et al, 2020) and internalize knowledge while allowing others to receive knowledge by listening to the answers. Course group work and/or discussion could also motivate knowledge sharing as in discussion, students exchange their ideas or reach decisions together.…”
Section: Lecturer Supportmentioning
confidence: 99%
“…Also, these inquisitive techniques help students to be actively involved in the teaching and learning process, as well as stimulate the mastery of higher-order thinking skills. These questioning skills help teachers in explaining the importance of a concept to allow students to understand and develop their thinking to a higher level [4].…”
Section: Introductionmentioning
confidence: 99%